Adapting CBT to treat depression in Armed Forces Veterans: qualitative study. Issue 5 (21st March 2019) - Farrand, Paul; Mullan, Eugene; Rayson, Kat; Engelbrecht, Alberta; Mead, Karen; Greenberg, Neil
Abstract: Background: The principles of the Armed Forces Covenant state that Armed Forces Veterans should be at no disadvantage resulting from their service compared with a general adult population. However, despite being at increased risk of experiencing common mental health difficulties, evidence indicates that 82% of Armed Forces Veterans receive no treatment, compared with 63% of the general adult population. Aim: To gain a better appreciation of factors that inform the type of adaptations to cognitive behavioural therapy (CBT) interventions for depression and mainstream service promotion materials to enhance acceptability for Armed Forces Veterans. Method: This is a qualitative study employing a focus group of 12 participants to examine the main impacts of depression on Armed Forces Veterans alongside attitudes towards terminology and visual imagery. Thematic analysis was used to identify themes and sub-themes with rigour established through two researchers independently developing thematic maps to inform a final agreed thematic map. Results: A behavioural activation intervention supporting re-engagement with activities to overcome depression had good levels of acceptability when adapted to reflect an Armed Forces culture. Preferences regarding terminology commonly used within CBT adapted for Armed Forces Veterans were identified. Concerns were expressed with respect to using imagery that emphasized physical rather than mental health difficulties. Conclusions: There is the need to consider the Armed Forces community as a specific institutional culture when developing CBT approaches with potential to enhance engagement, completion and recovery rates. Results have potential to inform the practice of CBT with Armed Forces Veterans and future research.